2021
DOI: 10.15586/jkcvhl.v8i3.173
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Renal Metastasis from Adenoid Cystic Carcinoma of the Nasal Cavity and Literature Review

Abstract: Adenoid cystic carcinoma (ACC) is a rare malignant cancer that arises from secretory glands. Slow growth, perineural invasion, and late recurrences are the main characteristics of ACC. Only few cases of kidney metastases from ACC have been reported in the literature. We report here the case of a 66-year-old female patient who presented with bilateral renal metastases from ACC of the nasal cavity, detected 14 years after treatment of primary tumor and 6 years after metastasectomy of lung metastases. Histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Maissa et al have suggested systemic chemotherapy agents such as cyclophosphamide, cisplatin, 5-fluorouracil and doxorubicin may have some efficacy against metastatic ACCs; however, chemotherapeutic management of renal metastases remains not well defined at present 30. Other treatment approaches such as thermoablation and renal embolisation have been proposed by Longo et al , predominantly from a palliative point of view and for the management of painful lesions 31…”
Section: Discussionmentioning
confidence: 99%
“…Maissa et al have suggested systemic chemotherapy agents such as cyclophosphamide, cisplatin, 5-fluorouracil and doxorubicin may have some efficacy against metastatic ACCs; however, chemotherapeutic management of renal metastases remains not well defined at present 30. Other treatment approaches such as thermoablation and renal embolisation have been proposed by Longo et al , predominantly from a palliative point of view and for the management of painful lesions 31…”
Section: Discussionmentioning
confidence: 99%